Economy and Planning of Ecotourism:: A case study in the Brazilian Cerrado - Cardoso, Maione Rocha de Castro; Cardoso, Gil Célio de Castro; Brito, João Marcelo Bersan Soares de (Sustainability in Debate, 2015)
Tourism is currently one of the main economic activities in Brazil, although its development implies a mix of positive and negative impacts on the local communities involved. In that regard, ecotourism appears as an option for the development of sustainable tourism and its correlated activities. This paper analyzes Ecotourism related policies and management in Pirenópolis/GO, in Central Brazil, and its effects on the local economy. Methodologically, a bibliographic and documental research was performed, and semi-structured interviews and field visits were conducted. Results point out at a very preliminary level of planning and management in the Ecotourism field. Concretely, very few actions have been taken in the context of the city plan for Tourism (Plano Municipal de Turismo, in Portuguese). The authors also identified a need to advertise ecotourism events and local attractions through wider reaching, democratic means of communications (like TV and radio) as well as the Internet in order to attract the public and to generate higher touristic revenues in the region.